Efficacy and safety of thread embedding acupuncture combined with conventional acupuncture for chronic low back pain: A study protocol for a randomized, controlled, assessor-blinded, multicenter clinical trial. Issue 21 (May 2018) - Leem, Jungtae; Kim, Hyunho; Jo, Hee-Geun; Jeon, Sae-rom; Hong, Yejin; Park, Yeoncheol; Seo, Byungkwan; Cho, Yeeun; Kang, Jung Won; Kim, Eun-Jung; Han, Ga Young; Kim, Jae Soo; et al.
Abstract: Background: Back pain is one of the most common diseases, and many patients with recurrent pain seek alternative treatment strategies. Thread embedding acupuncture involves thread insertion at the acupuncture point for continuous physical and chemical stimulation. Although thread embedding is widely used in clinical practice, there is no sound evidence of its efficacy for chronic back pain. We describe the protocol for a randomized controlled trial for investigation of the efficacy and safety of thread embedding acupuncture combined with conventional acupuncture for chronic low back pain. Methods: This randomized, controlled, assessor-blinded, 2-armed, parallel, multicenter clinical trial will include 38 outpatients with chronic low back pain recruited from 4 traditional Korean Medicine hospitals. The patients will be randomly allocated to a treatment group (conventional acupuncture + thread embedding acupuncture) and a control group (only conventional acupuncture) in a 1:1 ratio. The treatment group patients will receive thread embedding acupuncture treatment at 10 acupuncture points (multifidus muscle, 4 points; spinal erector muscles, four points; lumbar quadrate muscle, 2 points) once a week for 8 weeks (8 sessions). In addition, all patients will receive conventional acupuncture treatment at 14 acupuncture points (GV3, EX-B5, and bilateral BL23, BL24, BL25, BL26, BL40, and BL60) twice a week for 8 weeks (16 sessions). The primary outcome will be the change in the visual analog scale score from visit 1 to visit 16, analyzed by independent t tests, in both groups. The groups will also be compared with regard to the clinical relevance (minimal clinically important difference), quality of life (3-level version of Euroqol-5D), disability level (Roland and Morris Disability Questionnaire), global assessment (patient global impression of change), and safety. Cost data for cost–benefit and cost-effectiveness analyses will be collected. Discussion: Our study results will provide evidence of the efficacy and safety of thread embedding acupuncture combined with conventional acupuncture for the management of chronic low back pain. Even though the assessors will be blinded, the patients will not be blinded to treatment because of the lack of a sham embedding acupuncture group; this is a limitation of our study. Trial registration: Clinical Research Information Service: KCT0002666